2020
DOI: 10.1038/s41598-020-60476-7
|View full text |Cite
|
Sign up to set email alerts
|

EPDR1 up-regulation in human colorectal cancer is related to staging and favours cell proliferation and invasiveness

Abstract: The finding of novel molecular markers for prediction or prognosis of invasiveness in colorectal cancer (cRc) constitutes an appealing challenge. Here we show the up-regulation of EPDR1 in a prospective cohort of 101 CRC patients, in a cDNA array of 43 patients and in in silico analyses. EPDR1 encodes a protein related to ependymins, a family of glycoproteins involved in intercellular contacts. A thorough statistical model allowed us to conclude that the gene is significantly up-regulated in tumour tissues whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 41 publications
(49 reference statements)
0
17
0
Order By: Relevance
“…Afterward, Kirkland et al [ 6 ] also found a gene highly expressed in hematopoietic cells and several malignant tissues and cell lines, which was named MERP1 and turned out to be the same as UCC1. Lately, several studies [ 7 9 ] were reported that EPDR1 was closely related to pathological or developmental processes of various tumors including breast cancer (BRCA) [ 10 ], hepatocellular carcinoma (HCC) [ 11 ], colorectal cancer, and so on.…”
Section: Introductionmentioning
confidence: 99%
“…Afterward, Kirkland et al [ 6 ] also found a gene highly expressed in hematopoietic cells and several malignant tissues and cell lines, which was named MERP1 and turned out to be the same as UCC1. Lately, several studies [ 7 9 ] were reported that EPDR1 was closely related to pathological or developmental processes of various tumors including breast cancer (BRCA) [ 10 ], hepatocellular carcinoma (HCC) [ 11 ], colorectal cancer, and so on.…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, searching the TCGA, PanCancer Atlas database [21] for the candidate genes revealed that ADAMTS14 was not reported amongst the mutated genes; however, other ADAMTS isoforms were found to be mutated in these patients' samples, including ADAMTS 1, 6, 9, 12, and 16-19. Similarly, other ARHGAP isoforms were mutated in these patients (ARHGAP 5,6,18,21,(24)(25)(26)31,32,35,36,39,40,and 44). A deletion alteration in ARHGAP 22 was also reported in only 0.5% of patients (10q11.22-q).…”
Section: Resultsmentioning
confidence: 81%
“…The third proposed candidate, EPDR1 , was originally identified as a batokine with a potentially important role in metabolic regulation. Recently, overexpression of this protein was found to be positively correlated with colorectal cancer proliferation and invasiveness in a cohort study [ 32 ]. Similarly, high levels of EPDR1 are correlated with the advancement of hepatocellular carcinoma stages, making it a potential biomarker for disease progression and monitoring [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Gimeno-Valiente et al. ( 11 ) found that upregulation of EPDR1 in DLD1 and HCT116 cell lines was related to human colorectal cancer stage, and knockdown of EPDR1 could inhibit cell proliferation, migration, invasiveness, and adhesion to type I collagen fibers. Similar results were observed in human bladder cancer ( 17 ).…”
Section: Discussionmentioning
confidence: 99%
“…Although the function of EPDR1 has not been completely characterized, accumulating evidence suggests that EPDR1 is associated with various human diseases, particularly the initiation and progression of various human cancers ( 9 , 10 ). At present, EPDR1 has been reported to be differentially expressed in a variety of tumors and exerts an oncogenic role in colorectal cancer ( 11 ) and a tumor-suppressive role in breast cancer ( 12 ). However, the characterization of EPDR1 gene in EOC has not been reported.…”
Section: Introductionmentioning
confidence: 99%